MAGNETORHEOLOGICAL ELASTOMER ELASTICITY - BASED CAPACITOR - BUNOIU, O. M.; BICA, I.; CHIRIGIU, L.; CIRTINA, G.; IORDACONIU, L. (Studia Universitatis Babeș-Bolyai Physica, 2015)
In the present paper, a magnetorheological elastomer (MRE) based on silicone rubber, magnetorheological suspension and catalyst, in a magnetic field, is obtained. Using the plane capacitor method, it is shown that the elastic properties of the magnetorheological elastomer are influenced by the intensity and direction of the applied magnetic field. The obtained experimental results are presented and discussed.